PENGARUH UKURAN PERUSAHAAN, OPINI AUDIT DAN REPUTASI AUDITOR TERHADAP AUDIT REPORT LAG PADA KANTOR AKUNTAN PUBLIK WILAYAH JAKARTA SELATAN - Apriyanti; Dewi Rejeki (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
The purpose of this study is to prove the effect of company size, audit opinion and auditor reputation on audit report lag at KAP in South Jakarta which consists of junior auditors, senior auditors, supervisors and managers. The method used is a quantitative method by filling out a questionnaire. The data analysis technique used is descriptive statistics and hypothesis testing. The results of this study prove that company size, audit opinion and auditor reputation have a positive influence on audit report lag either partially or simultaneously.